THE EFFECT OF HUMAN DEVELOPMENT INDEX (HDI) GROSS REGIONAL DOMESTIC PRODUCT (GRDP) AND UNEMPLOYMENT ON POVERTY IN 4 PROVINCES IN SUMATRA ISLAND - Erbi Hamdani; Asnawi Asnawi (Journal of Malikussaleh Public Economics, 2023)
This study aims to determine the effect of the Human Development Index (IPM), Gross Regional Domestic Product (GRDP) and Unemployment on Poverty in 4 Provinces on the Island of Sumatra. The data used in this study is secondary data for 2007-2021 obtained from the Central Statistics Agency (BPS). The data analysis method used is panel data regression using Eviews 9 software. The results of this study indicate that the HDI used in this study has no negative and insignificant effect on the poverty of the 4 provinces on the islands of Sumatra, Aceh, Bengkulu, South Sumatra and Lampung, the GRDP in use in this study has a negative and significant effect on poverty in 4 provinces in Aceh, Bengkulu, Lampung and South Sumatra Provinces and unemployment used in this research has a positive and significant effect on increasing poverty in 4 provinces on the islands of Sumatra, Aceh, Bengkulu, Lampung and South Sumatra. The suggestion from this research is that the governments in the provinces of Aceh, Lampung, Bengkulu and South Sumatra should improve public services so that people will prosper and reduce poverty.